2005
DOI: 10.1007/978-3-540-31843-9_51
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Multi-user System for Simultaneous Graph Drawing

Abstract: Abstract. In this paper we consider the problem of simultaneous drawing of two graphs. The goal is to produce aesthetically pleasing drawings for the two graphs by means of a heuristic algorithm and with human assistance. Our implementation uses the DiamondTouch table, a multiuser, touch-sensitive input device, to take advantage of direct physical interaction of several users working collaboratively. The system can be downloaded at http://dt.cs.arizona.edu where it is also available as an applet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Recently, a new direction in the area of the graph drawing has been opened: Simultaneous planar graph drawing [1,[3][4][5][6]. Consider a set of objects with two different sets of relations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new direction in the area of the graph drawing has been opened: Simultaneous planar graph drawing [1,[3][4][5][6]. Consider a set of objects with two different sets of relations.…”
Section: Introductionmentioning
confidence: 99%
“…Kobourov and Pitta [20] presented an interactive multiuser system for drawing graphs simultaneously. Their system uses the help of the human viewer and a rudimentary crossing minimization heuristic to minimize the number of crossings in a straight-line drawing of two graphs simultaneously.…”
Section: Preliminariesmentioning
confidence: 99%
“…For non-planar graphs, force-directed techniques are used by Erten et al to define visualization schemes and design drawing heuristics where vertices shared by many graphs of the sequence are located in the center of the layout and edges shared by many graphs are not too long [16]. Kobourov and Pitta describe an interactive multi-user environment for simultaneous embedding where the number of edge crossings is kept under control by means of heuristic primitives [23]. Chimani et al further investigate the problem of minimizing the number of crossings in a simultaneous embedding; they show the NP-hardness of the question and experimentally compare heuristics and exact drawing algorithms [7].…”
Section: Graph Drawing Algorithmsmentioning
confidence: 99%
“…However, since G pag and G usr share the whole vertex set, the centrality of the shared vertices (considered in [16]) is not a meaningful aesthetic requirement in our case. Also, motivated by recent cognitive experiments, we do not insist on minimizing the number of edge crossings (as done in [7,23]) but rather we try to control the visual quality of the edge crossings. More precisely, human-computer interaction experiments have shown that orthogonal crossings do not inhibit human task performance when reading a drawing and that users have a geodesic tendency when discovering relations between pairs of vertices [20,21,22].…”
Section: Graph Drawing Algorithmsmentioning
confidence: 99%